2009
DOI: 10.1055/s-0029-1210605
|View full text |Cite
|
Sign up to set email alerts
|

The Nonenzymatic Glycation of Proteins and Nucleic Acids, Their Importance for the Development of Diabetic Complications, Possible Molecular Basis of Aging and Autoimmunological Processes

Abstract: The formation of nonenzymatic glycation products of proteins and nucleic acids appears to be a link between chronic hyperglycaemia and long-term diabetic complications and special forms of aging during normoglycaemia. The major effects of extended glycation include cross-linking of glycated proteins, attachment of soluble proteins to extracellular glycated matrices, conformational changes of proteins followed by altered functions and immunogenicity, and abnormalities in nucleic acid functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In vivo as well as in vitro studies have demonstrated the different collagen types to be nonenzymatically glycated with the result of altered functional properties. The basement membrane of the vessel wall containing collagens type IV and V is a main target of nonenymatic glycation in the course of the development of vascular lesions in longterm diabetes and atherosclerosis in advanced age (for review of the widely spread literature see Brownlee et al, 1981Brownlee et al, , 1984Cerami et al, 1985;Krantz et al, 1986).…”
Section: Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo as well as in vitro studies have demonstrated the different collagen types to be nonenzymatically glycated with the result of altered functional properties. The basement membrane of the vessel wall containing collagens type IV and V is a main target of nonenymatic glycation in the course of the development of vascular lesions in longterm diabetes and atherosclerosis in advanced age (for review of the widely spread literature see Brownlee et al, 1981Brownlee et al, , 1984Cerami et al, 1985;Krantz et al, 1986).…”
Section: Matrixmentioning
confidence: 99%
“…Over the last few years investigations in the field of nonenzymatic glycation of proteins have given evidences for the importance of nonenzymatically glycated proteins in the development of vascular complications in long-term diabetes and in atherosclerosis of nondiabetic origin (. Brownlee and Cerami, 1981;Browniec et al, 1984; Krantz et aL, 1986, for reviews).…”
Section: Introductionmentioning
confidence: 99%